Intellectual capital, knowledge sharing and equity crowdfunding - Vrontis, Demetris; Christofi, Michael; Battisti, Enrico; Graziano, Elvira Anna (My University, 2021)
Purpose: This paper explores knowledge sharing (KS) and intellectual capital (IC) impacts on the success rate of equity crowdfunding (EC) campaigns in the Italian market, which represents a new model for financing entrepreneurial initiatives. Design/methodology/approach: The relation between KS, IC and the success rate of EC campaigns is analysed with a panel regression that measures IC through the value added intellectual coefficient. Social network analysis is used to measure KS in the users' network on Twitter for EC campaigning. Specifically, the authors consider the information users exchange on social networks as a proxy of KS and identify the hubs influencing information dissemination, the size and strength of networks for each EC campaign. Finally, the success rate of EC campaigns is a ratio of the number of positive campaigns to the total number of campaigns for each platform. Findings: The success rate of EC campaigns is positively related to IC and significantly and positively related to the number of connections the EC platforms have. Practical implications: The positive relationship between the hub role of social network platforms and the success of EC campaigns provides an important signal to crowdfunding operators. As more potential investors focus on an EC campaign, a bandwagon effect could involve uninformed investors. This result is crucial in order to better understand how social media activity affects crowdfunding success. Originality/value: Although the literature has examined the impact of KS on general firm performance and the mediating role of intellectual capital, no prior studies have examined the impacts of KS and IC on the success rate of EC campaigns in a specific market.
Keywords: Entrepreneurial initiative; Equity crowdfunding; Intellectual capital; Knowledge sharing; Social media; VAIC™ model